Orthodontic management of traumatized teeth: a literature review - Hifny, Sara Ahmed; Hawsawi, Mohammed Abdulrazzag; Baraat, Abdulaziz Mohammed; Bakhadlaq, Wesam Faiz; Hakami, Hafiz Mohammed; Alghamdi, Abdullah Abdulghani; Alsayegh, Homood Mohammed; Ashour, Asmaa Tariq; Bahamid, Ahmed Abdullah; Alsalem, Rehan Salem; Jiffri, Shereen Osama (International Journal Of Community Medicine And Public Health, 2021)
Traumatic dental injuries can significantly impact the appearance and the functions of the affected teeth and can induce significant damages to the surrounding structures within the oral cavity including both the soft and hard ones. This present literature review aimed to discuss the appropriate orthodontic management of dental traumatic events and to present evidence from previous studies in the literature. The search took place in the relevant databases l, such as PubMed, Web of Science, Scopus and Google Scholar to find the relevant articles that have previously discussed the topic to retrieve all the potentially related information that will help to formulate strong evidence. The literature review was focused on the orthodontic management considerations for patients that had dental traumas including crown and crown-root fractures, in addition to intrusion and extrusion luxation injuries. Overall, orthodontists should be able to deal with all the possible traumatic lesions as early as possible to avoid the development of any complications which might affect the prognosis of the affected teeth and the surrounding structures. Moreover, the evidence suggested that aforementioned lesions which was a period of at least three months should be recommended after applying the orthodontic treatment to early screen against any potential complications and maintain stabilization.